The Effect of Psychological Factors on Investor Behavior in Amman Stock Exchange Market - Al-Taani, Dr. Khalaf .S.; Al - Zu'bi, Mohammed Khalaf Dawood (IJRDO - Journal of Business Management, 2017)
This study aims to examine the impact of psychological factors on the behavior of investors in Amman Stock Exchange by studying the factors influencing the behavior and trends of investors, including (rumors, community culture, personal experience, and herd behavior).To achieve the objectives of the study, the researchers adopted a descriptive analytical approach based on data collection and interpretation of the phenomenon through the development of a questionnaire consisting of (26) paragraphs distributed to a simple random sample of 30 investors dealing with Amman Stock Exchange, where the study population consisted of all investors including (individual Investors, economic institution, securities trading company) in Amman Financial Market. The researchers used the SPSS statistical program to analyze the results. The study concluded that there was a statistically significant effect of psychological factors on the behavior of the investor in the Amman Financial Market. The value of Rsquare (0.48) was statistically significant. In addition to the rumors, the culture of the society surrounding the investor, the behavior of the group, and reliance on personal experience are the most important factors affecting investment decisions. The study also showed that there is no correlation between the behavior of the investor and the personal and financial variables, and these results are consistent with the results of the study of (Habaka, Haddad, Hourani, Suzaida, Bakar, and Amelia).The researchers recommended a number of recommendations. The most important of these recommendations was the need to hold training workshops for investors by the managers of the Amman Financial Market in order to clarify the importance of psychological factors in influencing their investment behavior to prevent the drift behind rumors and tendency towards mass escape in sales or purchase, and to avoid the financial speculation